Multiple-viewing stories: Constructing expertise in online film evaluations through storytelling. (August 2020) - López Escarcena, Ignacio
Highlights: Narratives are used to construct expertise and to connect with other reviewers. Participants align with one another through shared knowledge and experience. Expertise is constructed interactionally and not individually. Abstract: The aim of this paper is to explore the discursive constructions of expertise that take place through narratives within a realm that, before the internet, used to belong to 'professional' film critics. By looking at a site where people discuss cinema — The Internet Movie Database (IMDb)—, I examine how digital spaces enable their users to express opinions on this topic, and, specifically, how these participants can present themselves within a type of narrative that I have categorised as multiple-viewing stories . As I argue, by telling stories, users discursively construct a type of expertise that is grounded on shared experience and knowledge. Thus, notions such as knowing participation come to the fore .